Mbili-Mbili crop configurations, a maize–bean–pigeon pea intercropping system for Eastern Africa - CGIAR Research Program on Water, Land and Ecosystems (2021)
Field trials have been conducted over the last 3 years. Maize yields are comparable to other common systems but pigeon pea yields are improved. Economic yields are favorable for the Mbili-Mbili system. Recently farmer perceptions/experiences data were obtained and evaluations of these data are ongoing.